2013
DOI: 10.1111/j.1538-4616.2012.00566.x
|View full text |Cite
|
Sign up to set email alerts
|

Deposit Insurance, Banking Crises, and Market Discipline: Evidence from a Natural Experiment on Deposit Flows and Rates

Abstract: Using evidence from Russia, we carry out what we believe to be the literature's cleanest test of the direct impact of deposit insurance on market discipline and study the combined effect of a banking crisis and deposit insurance on market discipline. We employ a difference‐in‐difference estimator to isolate the change in the behavior of a newly insured group (i.e., households) relative to an uninsured “control” group (i.e., firms). The sensitivity of households to bank capitalization diminishes markedly after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
1
5

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(87 citation statements)
references
References 29 publications
2
79
1
5
Order By: Relevance
“…17 16 Full results are available upon request. and Karas et al (2013) employed a similar projection of their results in their analyses of market discipline in the Turkish and Russian banking sector, respectively. 17 Fueda and Konishi (2007) show that depositor sensitivity in Japan was most significant in the period 1997-2001 despite the presence of a blanket guarantee.…”
Section: Before and After The 2001q1 Crisismentioning
confidence: 99%
See 2 more Smart Citations
“…17 16 Full results are available upon request. and Karas et al (2013) employed a similar projection of their results in their analyses of market discipline in the Turkish and Russian banking sector, respectively. 17 Fueda and Konishi (2007) show that depositor sensitivity in Japan was most significant in the period 1997-2001 despite the presence of a blanket guarantee.…”
Section: Before and After The 2001q1 Crisismentioning
confidence: 99%
“…Further, more than any other measure, the capital ratio is extensively used as a proxy for bank risk taking in market discipline studies, in both developed and emerging market economies (e.g., Hannan and Hanweck 1988, Park and Peristiani 1998, Martinez Peria and Schmukler 2001, Karas et al 2013, Berger and Turk-Ariss 2014. We also refer to and who found that only bank capital proved to be unambiguously leading to depositor discipline in the Turkish conventional banking market.…”
Section: Subsequently In December 2005 Anadolu Finans and Family Fimentioning
confidence: 99%
See 1 more Smart Citation
“…This does not imply that the findings of our experiment are only relevant to understanding the behavior of uninsured retail depositors or wholesale depositors. 10 Several recent studies emphasize that retail depositors have very limited knowledge about deposit insurance (Bartirolo, 2011;Sträter et al, 2008) and that even informed and insured depositors are likely to withdraw deposits from distressed banks (Iyer and Puri, 2012;Karas et al, 2013;Pyle et al, 2012). Moreover, the design provides an experimental counterfactual for discussions of a reduction of current levels of deposit insurance in the context of bank incentives.…”
Section: Ecb Working Paper 1711 August 2014mentioning
confidence: 99%
“…Our results confirm this conjecture, while at the same time clarifying which deposit insurance characteristics are most important for depositor confidence. In the paper that is perhaps most similar in spirit to ours, Karas et al (2013) compare the reactions of newly-insured and uninsured depositors to a 2004 minor panic in the Russian banking sector; in a related manner, our study attempts to compare the reactions of newlyinsured and historically-insured depositors to a hypothetical crisis that allows for a wider range of deposit insurance features and depositor attributes, and for consideration of counter-factual events. Overall, our quasi-experimental approach provides a fresh perspective on a well-travelled area by allowing us to ask new questions and re-investigate old answers.…”
Section: Introductionmentioning
confidence: 99%